Fischer-Tropsch synthesis over lignin-derived cobalt-containing carbon fiber catalysts prepared in a single step by electrospinning - Valero-Romero, María José; García-Mateos, Francisco José; Sun, Xiaohui; Kapteijn, Freek; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2022)
In the present, work submicron-sized cobalt-containing lignin fibers have been prepared by the electrospinning technique, using Alcell lignin as carbon precursor, a low-cost co-product of the paper making industry. Carbon fibers were obtained by carbonization of Co-containing lignin fibers at different temperatures, yielding cobalt nanoparticles very well dispersed on the carbon fibers surface. These fibrillar catalysts were tested for Low-Temperature FTS using different H2/CO ratios
Keywords: Combustibles sintéticos - Congresos; Biomasa - Combustibles - Congresos; Fischer-Tropsch, Procedimiento de - Congresos; Fischer-Tropsch synthesis; Co-containing carbon fibers; Lignin; Electrospinning